2015
DOI: 10.1038/ng.3396
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive 1000 Genomes–based genome-wide association meta-analysis of coronary artery disease

Abstract: Existing knowledge of genetic variants affecting risk of coronary artery disease (CAD) is largely based on genome-wide association studies (GWAS) analysis of common SNPs. Leveraging phased haplotypes from the 1000 Genomes Project, we report a GWAS meta-analysis of 185 thousand CAD cases and controls, interrogating 6.7 million common (MAF>0.05) as well as 2.7 million low frequency (0.005 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
1,449
0
5

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,141 publications
(1,533 citation statements)
references
References 84 publications
36
1,449
0
5
Order By: Relevance
“…Because not all variants could be retrieved by LDlink, we selected α=1×10 −4 to declare significance in this secondary analysis (an effective Bonferroni correction for 500 tests). We also looked up CEC association results for variants associated with blood lipid levels (n=160 single‐nucleotide polymorphisms [SNPs]) or CAD risk (n=86 SNPs) by GWAS,22, 23, 24, 25, 26 using a statistical threshold of α=2.1×10 −4 (Bonferroni correction for 239 different variants). For these secondary analyses of candidate variants, we did not correct for the number of CEC phenotypes and statistical models to assess statistical significance.…”
Section: Methodsmentioning
confidence: 99%
“…Because not all variants could be retrieved by LDlink, we selected α=1×10 −4 to declare significance in this secondary analysis (an effective Bonferroni correction for 500 tests). We also looked up CEC association results for variants associated with blood lipid levels (n=160 single‐nucleotide polymorphisms [SNPs]) or CAD risk (n=86 SNPs) by GWAS,22, 23, 24, 25, 26 using a statistical threshold of α=2.1×10 −4 (Bonferroni correction for 239 different variants). For these secondary analyses of candidate variants, we did not correct for the number of CEC phenotypes and statistical models to assess statistical significance.…”
Section: Methodsmentioning
confidence: 99%
“…The associations of 325 individual SNPs with testosterone in 3,225 men of European ancestry are reported by Jin et al. (2012); associations of 322 of these variants with CAD risk in 60,801 CAD cases and 123,504 controls are reported by the CARDIoGRAMplusC4D Consortium (2015). Previously, in an independent dataset, Coviello et al.…”
Section: Motivating Example: Serum Testosterone and Coronary Heart DImentioning
confidence: 99%
“…The joint forces of the CARDIoGRAM (Schunkert et al , 2011), C4D (Coronary Artery Disease C4D Genetics Consortium, 2011) and finally the CARDIoGRAMplusC4D (CARDIoGRAMplusC4D Consortium et al , 2013; Nikpay et al , 2015) consortium allowed the analysis of up to 180,000 individuals, about half of which had CAD. Interestingly, consequent studies revealed a strong relationship between the numbers of individuals investigated and the numbers of genome‐wide significant variants detected by the GWAS approach (Fig 1).…”
Section: Genome‐wide Association Studies In Coronary Artery Disease Amentioning
confidence: 99%
“…(B) The number of SNP s detected with genome‐wide significance after replication correlates with the number of individuals included in the discovery studies. Symbols denote the numbers of genotyped SNP s [dots: ≤ 500,000 SNP s (Samani et al , 2007; McPherson et al , 2007; Helgadottir et al , 2007; Myocardial Infarction Genetics Consortium, 2009; Erdmann et al , 2009; Tregouet et al , 2009; IBC 50K CAD Consortium, 2011; Lu et al , 2012); asterisks: 2,500,000 SNP s (Coronary Artery Disease C4D Genetics Consortium, 2011; Schunkert et al , 2011; CARDIoGRAMplusC4D Consortium et al , 2013); arrow: 940,000 SNP s (Nikpay et al , 2015)].…”
Section: Genome‐wide Association Studies In Coronary Artery Disease Amentioning
confidence: 99%
See 1 more Smart Citation